KARAKTERISTIK MANAJEMEN PENDIDIKAN BERBASIS SEKOLAH - Dolong, Jufri (Inspiratif Pendidikan, 2018)
Abstract: MBS is intended to increase school autonomy, determine what it needs to be taught, and manage the resources available to innovate. MBS also has great potential to create professional principals, teachers and administrators. Thus, schools will be responsive to the needs of each student and school community. Student achievement can be optimized through the direct participation of parents and community. MBS is one of the answers to the provision of regional autonomy in the field of education and has been invited in Law Number 20 Year 2003 regarding Sisdiknas Article 51 Paragraph (1) which reads, "Management of early childhood education units, primary education and secondary education implemented based on minimum service standards with the principle of school-based management.